Sekolah Ideal Bagi Pekerja Anak (Studi Kasus Pekerja Anak di Kawasan Ekonomi Khusus Mandalika) - Ni Made Novi Suryanti; Feryna Nur Rosydah; Nursaptini; Syafruddin; Suud; Baiq Yunia Rahma Dewi; Sukma Maulida (SOSIO EDUKASI Jurnal Studi Masyarakat dan Pendidikan, 2026)
Child labor remains a social issue that impacts the fulfillment of the right to education, especially in areas experiencing rapid economic growth, such as the Mandalika Special Economic Zone (KEK). Formal education, which is still rigid, is not fully able to accommodate the needs of students who must fulfill dual roles as students and workers. This study aims to analyze the perspectives of child workers regarding the ideal school and formulate a school model that is responsive to the needs of child workers in the Mandalika SEZ. The study used a qualitative case study approach. The research subjects consisted of five child workers still in elementary and junior high school, selected through purposive sampling techniques. Data were collected through interviews and documentation, then analyzed using the Creswell Spiral Analysis model. The results of the study revealed four main themes: school is seen as a path to the future, the ability of child workers to balance school and work, challenges in the school environment, such as stigma and bullying, and the need for child-worker-friendly schools. Based on these findings, the study formulated an ideal school model that includes a safe and discrimination-free learning environment, empathetic teachers, child-friendly facilities, socio-economic support, contextual learning, and collaboration between schools, families, government, and the business world. This model is expected to be an alternative policy in realizing ideal schools for child workers in the Mandalika Special Economic Zone.